The Struggle of Taxi Drivers as Depicted in Clifford Odets’s Waiting for Lefty - Esti Ariani (2010)
This thesis is focused on the struggle of the employees against the system in the workplace as portrayed in Clifford Odets’s Waiting for Lefty. By using Intrinsic theory and Marxist theory, this thesis has three basic questions. Firstly, what class structures emerge in the workplace are exhibited in Clifford Odets’s Waiting for Lefty. Secondly, what factors make the workers are aware to change their conditions. Third, how do the workers change their conditions as presented in Waiting for Lefty. The study finds that there are two classes in the workplace as presented in play. First is the employers (capitalist) and second is the workers (proletariats).The workers as the inferior of the employers have difficult lives. They are from various job sectors that get injustices in the workplace and in the union. Concerning to these conditions, the workers want to change that bad conditions to the better ones. They struggle to change their conditions. Initially they dismantle the union and ultimately they go to strike.